Prevalence of urinary tract infection and the molecular characterization with special reference to fim h gene in uropathogenic e. Coli isolated from urine samples at a tertiary care hospital - Sinha, Sarita; Yadav, Madhu; Kumar Verma, Rajesh; Afaq, Nashra; Srivastava, Divya (Journal of Neonatal Surgery, 2025)
BACKGROUND Urinary tract infections, or UTIs, are common diseases caused by bacteria that enter the urethra from the skin or rectum. Urinary tract infections account for the majority of hospital visits worldwide and are a significant contributor to morbidity and comorbidity in individuals with underlying medical disorders. Uropathogenic Escherichia coli (UPEC) express a multitude of virulence factors (VFs) to break the inertia of the mucosal barrier of the urinary tract UPEC strains are the most common pathogens, accounting for 85% and 50% of community and hospital-acquired UTIs. UPEC strains have unique virulence characteristics, including type 1 fimbriae, which can result in worsening of UTIs. AIM AND OBJECTIVE A study on prevalence of urinary tract infection of uropathogenic E.coli and the molecular characterization with special reference to fim H gene from urine samples. MATERIAL & METHODS This was a cross-sectional study carried out in the Department of Microbiology at a tertiary care hospital for a period of 12 months i.e, 2024 to 2025. A total of 200 Patients were screened from 600 clinical isolates where 200 were positive of all the age groups and both sex with indwelling urinary catheters for at least 2 days, who were suffering from the symptoms of UTIs (fever > 38ºC, urgency, frequency dysuria or suprapubic tenderness) were included in this study. The Antibiotic Susceptibility testing was performed according to the CLSI guidelines 2024. If delayed, samples were refrigerated and processed within 4-6 hrs. The identification, biochemicals and the AST pattern was done according to the CLSI guidelines 2024. The DNA was extracted using the Qiagen DNA Extraction kit and the FIM H gene was detected by the conventional PCR assay. RESULTS In the present study a total of 600 clinically suspected cases were screened out of which total 200 isolates was found positive for UTI infection . Therefore, the prevalence rate of UTI was found to be 33%. From the present study it was observed that the Females 114 (57%) were more affected with the infection as compared to the Males 86 (43%). It was also noted that the age group of 31-40 years of age followed by 41-50 years was affected the most. In the age group of 0-10 years, 11-20 years and above 71 years was the least affected with the infection. In the current study E.coli (31%) was the most common followed by Klebsiella spp.(24%), Pseudomonas aeruginosa (18%), Staphylococcus aureus (7.5%), Acinetobacter baumanii (9%), Proteus (5.5%), Enterococcus (5.5%). In the present study the resistant rate for Ampicillin was observed to be 75% followed by Co-trimoxazole (92.5%) . Imipenem and Nitrofurantoin were sensitive with 89%. There were other research investigators whose finding were parallel to the current study where Enterobacteriaceae showed high resistant to commonly used antimicrobials. In the current study there was fim H gene studied. In the fim H gene there were 165 (82.5%) positive cases and negative were 35 (17.5%). CONCLUSION This study found that UTIs were more common in women than in men. The most common symptoms, such as chills, dysuria, and abdominal pain, were reported in patients with urinary tract infections. Therefore, regular exams and strict adherence to antibiotic stewardship recommendations can lower the cost of UTI prophylaxis. By performing these routine tests, the expense of avoiding UTIs can be decreased.x